2013
DOI: 10.1002/jip.1398
|View full text |Cite
|
Sign up to set email alerts
|

Situationally Equivocal Eyewitness Evidence and the Violence of Crimes

Abstract: Eyewitness evidence is amongst the most important types of evidence in investigative and juridical proceedings. Yet, eyewitness evidence frequently derives from observations made under situationally equivocal conditions, including such factors as darkness and physical obstruction of view. The effect of the violence of a given crime on potential jurors' evaluation of such equivocal evidence was addressed. A witness's identification of a suspect in a violent crime was generated in three versions, varying only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Despite the widespread use and influence of crime re-enactment videos within criminal justice systems around the world, no research yet has investigated the effect of crime reenactments on eyewitness memory. This is surprising, given that research has consistently demonstrated the fallibility of memory, such that memory can decay rapidly and change over time (Sharps, Herrera, & Price-Sharps, 2014). Additionally, the problems with eyewitness memory have been highlighted by the contribution of eyewitness misidentifications to cases of wrongful conviction, whereby over 70% of wrongful convictions overturned by DNA evidence involved faulty eyewitness identification (Innocence Project, 2015).…”
mentioning
confidence: 99%
“…Despite the widespread use and influence of crime re-enactment videos within criminal justice systems around the world, no research yet has investigated the effect of crime reenactments on eyewitness memory. This is surprising, given that research has consistently demonstrated the fallibility of memory, such that memory can decay rapidly and change over time (Sharps, Herrera, & Price-Sharps, 2014). Additionally, the problems with eyewitness memory have been highlighted by the contribution of eyewitness misidentifications to cases of wrongful conviction, whereby over 70% of wrongful convictions overturned by DNA evidence involved faulty eyewitness identification (Innocence Project, 2015).…”
mentioning
confidence: 99%